Effects of Pioglitazone on Nonalcoholic Fatty Liver Disease in the Absence of Constitutive Androstane Receptor Expression - Hwa Young Ahn; Hwan Hee Kim; Ji-Yeon Hwang; Changhun Park; Bo Youn Cho; Young Joo Park (PPAR Research)
Nonalcoholic fatty liver disease or steatohepatitis (NAFLD/NASH) is a fatty liver disease that is closely related to obesity, diabetes, and dyslipidemia. Pioglitazone, which was developed as an antidiabetic drug, is known to improve NALFD. Pioglitazone is metabolized by multiple cytochrome P450 (CYP) enzymes, which are regulated by the xenobiotic receptor constitutive androstane receptor (CAR). In this study, we investigated the effects of pioglitazone on NAFLD by absence of CAR activity under high-fat (HF)-fed conditions. CAR-/- mice showed significant improvement in NALFD after 12 weeks of pioglitazone treatment compared to wild-type mice. This improvement in NAFLD persisted in CAR-/- mice regardless of blood pioglitazone concentration. The expression of lipogenesis genes in the liver, sterol-regulatory element binding protein-1c (SREBP-1c), and stearoyl-CoA desaturase (SCD)-1 was decreased after pioglitazone treatment in HF-fed CAR-/- mice. In addition, the expression of peroxisome proliferator-activated receptor gamma 2 (PPARγ2) was decreased by pioglitazone in HF-fed CAR-/- mice. Changes in SREBP-1c and PPAR γ2 remained constant over short-term (6 h) pioglitazone and lipid injection. Our results showed that NAFLD was improved significantly by pioglitazone in a CAR deletion state. These results might be valuable because they suggest that interaction with CAR and pioglitazone/PPARγ2 may be important in regulating gene expression associated with NAFLD.